Liquid Wastes: the case of beauty parlors - Castillo Cortés, Marcela; Coto Campos, Juana María; Herrera Núñez, Jacqueline (Uniciencia, 2012)
The main objective of this preliminary study was to identify strengths and weaknesses of wastewater management in five beauty parlors to sustain further studies. Additionally, in two of the beauty parlors, S1 and S2, a representative wastewater sample during one day of labor was collected. The average values of pH, ammonium, COD and fats and oils were respectively: 7,96 ± 0,01; 0,38 ± 0,01 mg N/L; 77 ± 13 mg O2/L and 1905,0 ± 0,1 mg/L, for S1 and 8,88 ± 0,01; 57,4 ±0.2 mg N/L, 240 ± 128 mg O2/L and 2775,0 ± 0,1 mg/L, for S2. The fulfillment of the water quality standards is dependent of the type of products (biodegradable or not, with or without ammonia). Even though the volumes of discharge are intermittent and small, they generate negative impacts to the environment.